Masa Depan Pesantren di Indonesia : Analisis SWOT - Amilin Agustin; Lailatul Khofifah; Nurul Nurul; Debi Yansyah; Agus Rifki Ridwan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Pesantren is a traditional Islamic educational institution that has played a central role in character formation and the dissemination of Islamic values ​​in Indonesia. Along with the development of the times, pesantren are faced with the challenges of modernization, globalization, and rapid social change. This article analyzes the future of pesantren in Indonesia using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. The results of the analysis show that by utilizing internal strengths and external opportunities, and overcoming weaknesses and threats, pesantren can continue to be relevant and contribute to national development.